Feature Papers in Horticulturae - Archbold, Douglas D. (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Several of the 17 papers in this volume represent diverse strategies for improving sustainability in crop production systems. The maintenance of soil quality and the reclamation of marginal soils, improving tolerance to saline irrigation water, biodegradable alternatives to black plastic mulch, use of natural plant extracts against bacterial disease, and development of cultivars resistant to herbivorous arthropods address urgent priorities in sustainable systems. Two papers examine the driving forces and effects of adopting innovative agricultural technologies in food value chains in underdeveloped regions of the world, and identification of new Asian vegetable crop species for European environments and markets. Three papers reported on managing fruit set and ripening in important fruit crop species like orange, apple, and plum. Postharvest techniques to reduce disease and maintain fruit nutraceutical content were reported in separate papers. Classification techniques, conservation and utilization of unique plant species, and in vitro propagation techniques of species with potential horticultural value were described in four papers.